Digital tools and social-ecological sustainability. Going beyond mainstream ways of understanding the roles of tools in contemporary eduscapes - Almén, Lars; Bagga-Gupta, Sangeeta (Frontiers in Education, 2023)
All education in Sweden, or the Swedish eduscape, is permeated by discourses of compensation and inclusion, conceptualized in this study as a one-school-for-all ethos or perspective. This ethos contributes to a social-ecological framing, wherein the intentions are a society where everyone can participate as active members. The study presented in this paper scrutinizes the governmental strategy of 2017 to digitalize the Swedish educational system based on a one-school-for-all perspective. The study is framed by SWaSP (Second Wave of Southern Perspective) theoretical ideas, with a special focus on positionings, languaging, timespaces, epistemological-methodological dimensions, including ethics based on the entangled tenets of sociocultural, integrationist, southern perspectives. Furthermore, the study is anchored in three research projects and one societal developmental project. Materials from these projects have been generated through (n)ethnographic methods from different institutions in the Swedish educational landscape i.e., eduscape. These span across compulsory schools to Swedish for Immigrants, SFI, within Municipal Adult Education. Three themes have emerged in the multi-scalar data analysis from across settings: (i) intended inclusion, (ii) unintended exclusion, and (iii) intended exclusion. The first theme highlights how digital tools (DTs) create inclusion for students with special needs, or those who are new to the named-language Swedish, in the classroom community, thus, contributing to social-ecological sustainability. The second theme illustrates how DTs intended for inclusion in classroom practices morph into tools of exclusion for individuals in mainstream classrooms. The third theme highlights how students in the Swedish eduscape are intentionally excluded from mainstream classrooms. We argue that a social-ecological sustainable stance troubles the division of eduscapes into “mainstream” and “other” settings in contemporary societies, calling for the inclusion of all students irrespective of their positionalities. Our findings highlight that multimodal use of DTs potentially can facilitate inclusion, by providing tools where individual students can participate in and contribute to teaching and learning – what we frame as a third position of classroom organization.